Electing the President - Feinberg, Barbara Silberdick (New York Twenty-First Century Books, 1995)
Discusses the presidential election process including primaries, nominations, national conventions, campaigns, and the electoral college.
10 - 12 years
Keywords: Presidents -- Election -- Juvenile literature. -- United States; Presidents -- Election